Instrumental- and Emotion-Focused Care Work During Physical Health Events: Comparing Gay, Lesbian, and Heterosexual Marriages - Umberson, Debra (J Gerontol B Psychol Sci Soc Sci, 2017)
OBJECTIVES: We consider emotion- and instrumental-focused care work and marital stress during significant physical health events in midlife gay, lesbian, and heterosexual marriages. METHOD: We employ the factorial method, an extension of the actor–partner interdependence model, to analyze survey data from 808 midlife gay, lesbian, and heterosexual spouses in 404 unions. RESULTS: The amount of emotion- and instrumental-focused care work provided during physical health events, and the associations between care work and marital stress, depends on the gender of the respondent, gender of the spouse, and whether spouses are in a same-sex or different-sex union. For example, in both same- and different-sex marriages, women report providing more emotion-focused care work during their own health event than do men, and respondents report more health-related marital stress when the patient is a woman. DISCUSSION: Investigating how midlife same-sex and different-sex spouses care for each other during a spouse’s health event expands understandings of gendered aging experiences within marriage. Findings can elucidate health policies and clinical strategies that best support the health of men and women in same- and different-sex marriages.